Meibomian Glands and Tear Film Findings in Type 2 Diabetic Patients: A Cross-Sectional Study - Wu, Huping; Fang, Xie; Luo, Shunrong; Shang, Xumin; Xie, Zhiwen; Dong, Nuo; Xiao, Xianwen; Lin, Zhirong; Liu, Zuguo (Frontiers in Medicine, 2022)
Background: The characteristics of meibomian gland and tear film in type 2 diabetics with different glycemic control levels and diabetic durations remains largely unexplored. This study aimed to identify the association of dry eye and meibomian gland dysfunction (MGD) in type 2 diabetics. Methods: Ninety-nine patients with type 2 diabetes mellitus (DM group), thirty-three dry eye patients without diabetes mellitus (DE group) and forty normal subjects (NC group) were recruited. Participants were evaluated with an Ocular Surface Disease Index (OSDI) questionnaire, tear film breakup time (BUT), Schirmer I test (SIT), corneal fluorescein staining (FL), lipid layer thickness (LLT), and MGD parameters. Glycosylated hemoglobin (HbA1c) and duration of diabetes were recorded. Results: The SIT value in DM group was higher than that of DE group (P<0.05). The BUT and LLT were lower, and MGD parameters were higher in DM group than those of DE and NC groups (P<0.05). In DM group, 47 patients were diagnosed with dry eye (DM+DE group), while 40 patients without dry eye serves as DM-DE group. The SIT, BUT and LLT in the DM-DE group were higher (P<0.01), and MGD parameters were lower (P<0.01) than those of DM+DE group. The MGD parameters were higher in DM-DE group than NC group (P<0.05). The HbA1c levels were correlated with OSDI, BUT, LLT, FL and MGD parameters (P<0.001) in DM group. However, in patients with low HbA1c, normal SIT value and low OSDI, the MGD parameters were higher than those in NC (P<0.05). The duration of diabetes was positively correlated with MGD parameters (P<0.001). Conclusion: Asymptomatic MGD may be an early sign of dry eye and ocular discomfort in type 2 diabetics. The MGD parameters were associated with HbA1c level and diabetic duration.